Histopathology of the nail : onychopathology - Haneke, Eckart; Taylor and Francis (Boca Raton, FL : Routledge, an imprint of Taylor and Francis, 2017)
This comprehensive review of the histopathology of the human nail will act as a masterclass for all dermatologists, dermatopathologists, and nail-interested pathologists who have to interpret histological sections of nail tissue, which can be challenging for many reasons. In addition to a wealth of illustrated examples, the text guides the reader through the specialized terminology of nail science and supplies clinical data to help reach a reliable histopathological diagnosis.
chapter 1 Development, structure, and function of the nail -- chapter 2 Technical aspects -- Nail biopsies, handling, processing, sectioning, staining, and reading the slides -- chapter 3 Inflammatory dermatoses affecting the nail -- chapter 4 Infections and infestations affecting the nail -- chapter 5 Nail changes in systemic diseases and drug reactions -- chapter 6 Genodermatoses affecting the nail -- chapter 7 Nail specific conditions -- chapter 8 Epithelial and fibroepithelial tumors -- chapter 9 Fibrous tumors -- chapter 10 Vascular tumors -- chapter 11 Tumors with adipocyte, myxoid, muscular, osseous, and cartilaginous features -- chapter 12 Neurogenic tumors -- chapter 13 Histiocytic lesions -- chapter 14 Hematogenous tumors -- chapter 15 Melanocytic lesions -- chapter 16 Metastases of the digital tip.
Keywords: Nails (Anatomy) -- Histology; Nails (Anatomy) -- Pathophysiology; Nails (Anatomy) -- Diseases